Entrepreneurship dynamics in countries with highly volatile economies: a contextual study of South Africa and Zimbabwe - Magama, Faustinah (My University, 2015)
Entrepreneurship dynamics has been studied over the past years and until now, most questions remain unanswered and issues remain unresolved. The context of the study is mainly based on how entrepreneurs manage to operate successful ventures in volatile economies such as those of South Africa and Zimbabwe. Entrepreneurship dynamics research relating to highly volatile economies has not been done to a large extent. Certain research problems covered focus on certain aspects such as whether the ventures had been successful or were affected by the economic conditions of the country. A theoretical framework of entrepreneurship dynamics in highly volatile economies was developed. It analyses data across all industrial sectors in the above mentioned countries. The study targeted only existing entrepreneurs mainly operating in the formal sector of the economy to obtain real entrepreneurial challenges and strategies, as well as opinions relating to entrepreneurial activities. The study used judgemental sampling to collect data from a sampling frame of 194 entrepreneurs based in South Africa and Zimbabwe. The study used mixed methodology in order to analyse the data by performing both quantitative and qualitative studies. This was useful for the study as it managed to get open-end responses from entrepreneurs and how their businesses were affected by the countries’ economic conditions. In the qualitative analysis, qualitative themes were obtained from the data and some useful facts stated by entrepreneurs were noted. In the quantitative analysis, multiple regression was performed after validity and reliability tests were performed and results showed significant relationships of challenges, factors, trading, survival strategies and informal and formal sectors to entrepreneurial activities. Major findings consist of how highly volatile economies negatively impact entrepreneurial activities, how challenges have a negative impact on entrepreneurial activities and how the strategies implemented by entrepreneurs have a positive influence on entrepreneurial activities. Moreover, it has been perceived that due to highly volatile economies, people partake in entrepreneurial activities in the informal economic sector rather than the formal economic sector. The results of the study show that there are were mixed responses from the entrepreneurs themselves with regards to which economical sector they prefer operating in, as the quantitative results showed that entrepreneurs prefer operating in the formal economic sector. The qualitative themes mainly stated reasons why entrepreneurs operate in their respective economic sector. The study contributes in the area of entrepreneurship positively by adding on to the existing research. It also aims to provide reliable data that may be used in decision making by country officials, policy makers, educational institutions, traders, entrepreneurs, economists and traders. Economic volatility has had a great influence on entrepreneurship activities in certain countries. The contribution of the study is that of entrepreneurship research in terms of economic volatility’s relationship with entrepreneurship. It adds to the level of determining how the economy affects a country’s entrepreneurial activities.